2017
DOI: 10.1097/mbp.0000000000000299
|View full text |Cite
|
Sign up to set email alerts
|

Office blood pressure measurement alone often misclassifies treatment status in children with primary hypertension

Abstract: Objective Clinicians frequently rely on office blood pressure (BP) measurements alone to assess hypertension control, despite widespread acceptance of 24-hour ambulatory blood pressure monitoring (ABPM) as the reference standard in the initial diagnosis of hypertension. This study was designed to investigate how often the hypertensive status differed between concurrent office BP versus ABPM measurements, and whether any patient-specific characteristics predict the risk for misclassification by office BP. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
(13 reference statements)
0
7
1
2
Order By: Relevance
“…Conversely, Macumber et al reported that SBP levels were similar between the obese and lean groups (22). Moreover, Samuel et al showed that there were no significant relationship between the differences OBP-ABPM values and BMI (23). Similarly, we could not show significant correlations between BMI and the differences OBP-ABPM values in our patients.…”
Section: Discussioncontrasting
confidence: 76%
“…Conversely, Macumber et al reported that SBP levels were similar between the obese and lean groups (22). Moreover, Samuel et al showed that there were no significant relationship between the differences OBP-ABPM values and BMI (23). Similarly, we could not show significant correlations between BMI and the differences OBP-ABPM values in our patients.…”
Section: Discussioncontrasting
confidence: 76%
“…BP was assessed by ABPM, and we previously demonstrated that the ABPM diagnostic classification differed from the office BP classification in nearly 40% of visits. 30 Repeated ABPM was well tolerated by children with hypertension; .85% of monitorings were returned with a sufficient number of readings. Use of ABPM contributes to the frequent difference between pretrial and posttrial medication because pretrial therapy was often based on office BP readings, as is clinical practice.…”
Section: Figurementioning
confidence: 95%
“…not only BP <958 when measured by a physician, but also 958 when checked at home with a more than 25% difference between the two measurements). 18 White-coat hypertension is common in children with obstructive sleep apnoea syndrome, while masked hypertension can be found in renal transplant recipients. 19,20 AAP guidelines suggest using a 24-h ambulatory blood pressure monitor (ABPM) as the only reliable way to overcome these issues or when BP is borderline.…”
Section: Definition Of High Blood Pressure In Childhoodmentioning
confidence: 99%